2018
DOI: 10.1002/htj.21358
|View full text |Cite
|
Sign up to set email alerts
|

Lie symmetry analysis and numerical solutions for thermosolutal chemically reacting radiative micropolar flow from an inclined porous surface

Abstract: Steady, laminar, incompressible thermosolutal natural convection flow of micropolar fluid from an inclined perforated surface with convective boundary conditions is studied. Thermal radiative flux and chemical reaction Nomenclature: , buoyancy ratio parameter; , Biot number; , Concentration of the solute (mol m −3 ); , skin friction coefficient; , real numbers; , wall couple stress; , specific heat at constant pressure (J Kg −1 K −1 ); ∞ , free stream concentration (mol m −3 ); , molecular diffusivity of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The thermophysical aspects of magnetohydrodynamic (MHD) viscoinelastic fluid over a stretching surface were recently presented by Hussain et al 31 The study of convective heat and mass transfer in a MHD flow regime is important because of its usage in various natural phenomena and engineering applications, such as plasma studies, porous insulations, spreading of pollutants, and so forth. The diverse applications of heat and mass transfer flows have stimulated the researchers 32‐41 to investigate their dynamics in the presence of an external magnetic field. In recent years, the investigation of Hall current effect on MHD flows has been given more importance because in many industrial and practical applications, applied magnetic field is very strong or fluid is highly ionized.…”
Section: Introductionmentioning
confidence: 99%
“…The thermophysical aspects of magnetohydrodynamic (MHD) viscoinelastic fluid over a stretching surface were recently presented by Hussain et al 31 The study of convective heat and mass transfer in a MHD flow regime is important because of its usage in various natural phenomena and engineering applications, such as plasma studies, porous insulations, spreading of pollutants, and so forth. The diverse applications of heat and mass transfer flows have stimulated the researchers 32‐41 to investigate their dynamics in the presence of an external magnetic field. In recent years, the investigation of Hall current effect on MHD flows has been given more importance because in many industrial and practical applications, applied magnetic field is very strong or fluid is highly ionized.…”
Section: Introductionmentioning
confidence: 99%
“…Machireddy 44 discussed the impression of radiation on an MHD flow. Some recent studies on heat transfer are given in references 45‐48 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, for the approximate solution, numerical computation is performed to find results using fourth‐order Runge‐Kutta method with shooting technique carried out in MATLAB, taking a step length of 0.01 and error bound of 10 −3 . The detail of mathematical computations is presented in studies reported in References [30,31]. The impact of requisite characteristics of active parameters on velocity, temperature and concentration is presented.…”
Section: Solution Procedures and Validationmentioning
confidence: 99%